Nutrient allocation strategies of woody plants: an approach from the scaling of nitrogen and phosphorus between twig stems and leaves - Yan, Zhengbing (Sci Rep, 2016)
Allocation of limited nutrients, such as nitrogen (N) and phosphorus (P), among plant organs reflects the influences of evolutionary and ecological processes on functional traits of plants, and thus is related to functional groups and environmental conditions. In this study, we tested this hypothesis by exploring the stoichiometric scaling of N and P concentrations between twig stems and leaves of 335 woody species from 12 forest sites across eastern China. Scaling exponents of twig stem N (or P) to leaf N (or P) varied among functional groups. With increasing latitude, these scaling exponents significantly decreased from >1 at low latitude to <1 at high latitude across the study area. These results suggested that, as plant nutrient concentration increased, plants at low latitudes showed a faster increase in twig stem nutrient concentration, whereas plants at high latitudes presented a faster increase in leaf nutrient concentration. Such shifts in nutrient allocation strategy from low to high latitudes may be controlled by temperature. Overall, our findings provide a new approach to explore plant nutrient allocation strategies by analysing the stoichiometric scaling of nutrients among organs, which could broaden our understanding of the interactions between plants and their environments.